The Effect Tax of : Hotel, Revenue, Restaurant, Entertainment, Advertisement, Street Lighting, and Parking on Local Revenue of Greater Malang - Lestari Sukartiningsih, Lis (International Journal of Educational Research & Social Sciences, 2022)
Regional taxes are mandatory contributions to the region that are owed by individuals or entities that are coercive based on the law by not getting compensation directly and are used for regional needs for the prosperity of the people. This study aims to examine the effect of hotel tax revenue, restaurant tax, entertainment tax, advertisement tax, street lighting tax, and parking tax on the local revenue of Malang Raya. The population in this research is the Realization Report of Regional Original Income and Regional Tax Realization Report for the 2014-2018 period with the research sample census method. The results of the analysis using the SEM-PLS model. Hotel tax revenue, restaurant tax, entertainment tax, advertisement tax, and street lighting tax have a significant effect on local revenue. Meanwhile, parking tax revenue does not affect regional original income. Revenue from street lighting tax has the most influence on the local revenue of Malang Raya.